2004
DOI: 10.1177/0272431604268710
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Stressful Experiences, Self-Evaluations, and Self-Standards as Predictors of Sexual Activity During Early Adolescence

Abstract: Stressful experiences, self-evaluations, and self-standards associated with multiple contexts of development (i.e., school, family, sports/athletics) were investigated as predictors of initiation of sexual activity during the transition to adolescence. A sample of 134 seventh and eighth graders was followed as part of a 4-wave, 2-year longitudinal study. Survival analysis was used to examine measures at Time 1 as predictors of the timing of initiation of sexual activity. Reports of greater stressful experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…They listed experiences with urban hassles at similar levels to those reported from previous research with urban African American youth (DuBois, 2002; Grant et al, 2000; Waller, 2004). …”
Section: Discussionmentioning
confidence: 70%
“…They listed experiences with urban hassles at similar levels to those reported from previous research with urban African American youth (DuBois, 2002; Grant et al, 2000; Waller, 2004). …”
Section: Discussionmentioning
confidence: 70%
“…There is some evidence to suggest that the global measures of self-esteem used in prior research mask more precise relationships that exist between particular domains of self-esteem and adolescent sexual behavior (e.g., Waller & Dubois, 2004). The current study made use of three domains that have been shown to be important for adolescent attraction and romantic relationships.…”
Section: Sexual Selection Theorymentioning
confidence: 96%
“…Sample sizes ranged from 34 (Romo, Lefkowitz, Sigman, & Au, 2002) to 7965 (Longmore et al, 2004), resulting in a total of over 30,000 participants. Fourteen studies had sample sizes above 500 even after a high attrition rate across studies (median attrition rate = 37%), and 5 studies had sample sizes under 200 (French & Dishion, 2003;Halpern, Udry, & Suchindran, 1998;McBride et al, 2003;Romo et al, 2002;Waller & Dubois, 2004) Nine studies were from three independent U.S. national samples (Longmore, Manning, & Giordano, 2001;Longmore et al, 2004;McNeely et al, 2002;Meier, 2003;Mott, Fondell, Hu, Kowaleski-Jones, & Menaghan, 1996;Raffaelli & Crockett, 2003;Schvaneveldt et al, 2001;Sieving et al, 2000). Other studies represented a range of areas of the U.S., with half (n = 13) of the 26 studies with non-national samples including a high proportion of ethnic minority adolescents and the other 13 including mostly white adolescents.…”
Section: Overview Of the Literature Search And Included Studiesmentioning
confidence: 99%